EJBM 2020
DOI: 10.7176/ejbm/12-2-08
|View full text |Cite
|
Sign up to set email alerts
|

Moonlighting: An Antecedent to Job Commitment Between Academic Staff and Medical Doctors in Southwest Nigeria

Abstract: This study investigated the effects of moonlighting on job commitment between academic staff and medical doctors in Southwest Nigeria. The study employed descriptive research design and multi-stage sampling technique to select the respondents. Questionnaire was adopted as the research instrument and it was administered to 393 academic staff and 348 medical doctors respectively across various Universities and hospitals in Southwest, Nigeria. The returned questionnaire were coded in Excel and IBM SPSS 23 version… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, it is also associated with depletion in some cases, particularly when the primary job already demands long hours (Campion et al, 2020). Several studies have investigated the causes and consequences of teacher moonlighting, including in public sector universities in the provinces of Punjab and Federal Capital in Pakistan (Ara et al, 2016), among academic staff and medical doctors in Southwest Nigeria (Arogundade, 2020), and in US schools in the mid-1980s (Ballou, 1995). Studies have shown that moonlighting can lead to superficial teaching, limited personal contact with students, reduced concentration on daily teaching activities, and increased risk of burnout (Mumbere Kisumano & Safary, 2017).…”
Section: Teacher's Moonlightingmentioning
confidence: 99%
See 4 more Smart Citations
“…However, it is also associated with depletion in some cases, particularly when the primary job already demands long hours (Campion et al, 2020). Several studies have investigated the causes and consequences of teacher moonlighting, including in public sector universities in the provinces of Punjab and Federal Capital in Pakistan (Ara et al, 2016), among academic staff and medical doctors in Southwest Nigeria (Arogundade, 2020), and in US schools in the mid-1980s (Ballou, 1995). Studies have shown that moonlighting can lead to superficial teaching, limited personal contact with students, reduced concentration on daily teaching activities, and increased risk of burnout (Mumbere Kisumano & Safary, 2017).…”
Section: Teacher's Moonlightingmentioning
confidence: 99%
“…Moonlighting can have both positive and negative effects on employees and their organisations, and the nature of the impact can vary depending on the specific context (Arogundade, 2020; Fröhlich et al, 2013; Scott et al, 2020). On the one hand, moonlighting can provide employees with additional financial resources, skills, and experiences, which can help them to achieve their personal and professional goals (Averett, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations